Rates of new HIV diagnoses among Indigenous peoples in Canada, Australia, New Zealand, and the United States: 2009–2017. (1st August 2021) - Koehn, Katrina; Cassidy-Matthews, Chenoa; Pearce, Margo; Aspin, Clive; Pruden, Harlan; Ward, James; Mullen, Marama; Hogg, Robert S.; Nicholson, Valerie
Abstract : Objective: To compare rates and trends of HIV diagnoses among Indigenous peoples in Canada (First Nations, Métis, Inuit, and other non-specified), Australia (Aboriginal and Torres Strait Islanders), the USA (American Indian, Alaska Native, Native Hawaiian, and Other Pacific Islanders), and New Zealand (Māori). Design: We employed publicly available surveillance data from 2009 to 2017 to estimate the rate per 100 000 of HIV diagnoses. Estimated annual percentage change (EAPC) in diagnosis rates was calculated using Poisson regression. Setting: The four countries have passive population-based HIV surveillance programs. Participants: Population estimates from respective census programs were used as rate denominators. Main outcome measures: Estimated annual HIV diagnosis rate per 100 000 and EAPC were calculated for total Indigenous peoples, women, and men. Results: As of 2017, rates of HIV were highest in Canada (16.22, 95% confidence interval (CI): 14.30--18.33) and lowest in New Zealand (1.36, 95% CI: 0.65--2.50). Australia had a rate of 3.81 (95% CI: 2.59--5.40) and the USA 3.22 (95% CI: 2.85--3.63). HIV diagnosis rates among the total Indigenous population decreased in Canada (−7.92 EAPC, 95% CI: −9.34 to −6.49) and in the USA (−4.25 EAPC, 95% CI: −5.75 to −2.73) but increased in Australia (5.10 EAPC, 95% CI: 0.39--10.08). No significant trends over time were observed in New Zealand (2.23 EAPC, 95% CI: −4.48 to 9.47). Conclusion: Despite limitations to conducting cross-national comparisons, there are substantial differences in HIV diagnosis rates in these four countries that may be reflective of divergent national policies and systems that affect the health status of Indigenous peoples. Abstract : Supplemental Digital Content is available in the text